2020
DOI: 10.1186/s12961-020-00569-x
|View full text |Cite
|
Sign up to set email alerts
|

Multisector nutrition gains amidst evidence scarcity: scoping review of policies, data and interventions to reduce child stunting in Afghanistan

Abstract: Background: Child health indicators have substantially improved across the last decade, yet Afghanistan has among the highest child stunting and malnutrition rates in Asia. Multisectoral approaches were recently introduced but evidence for this approach to improve support for and implementation of child nutrition programmes is limited compared to other countries. Methods: We reviewed policy and programme data to identify best practices and gaps surrounding child malnutrition in Afghanistan. We conducted a scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Learning from other countries, almost all of them have taken a long time to see the impact of implemented convergence policies on stunting reduction, such as Peru, Thailand, Vietnam, Brazil, and PNG [ 37 , 38 ]. This also occurred in Afghanistan—at the beginning of the implementation of the convergence, there was no uniformity for nutrition-specific and -sensitive intervention activities in the community, although the government’s political commitment began to increase [ 39 ]. Another obstacle in implementing the convergence policy at the sub-district level is that they do not manage finances.…”
Section: Discussionmentioning
confidence: 99%
“…Learning from other countries, almost all of them have taken a long time to see the impact of implemented convergence policies on stunting reduction, such as Peru, Thailand, Vietnam, Brazil, and PNG [ 37 , 38 ]. This also occurred in Afghanistan—at the beginning of the implementation of the convergence, there was no uniformity for nutrition-specific and -sensitive intervention activities in the community, although the government’s political commitment began to increase [ 39 ]. Another obstacle in implementing the convergence policy at the sub-district level is that they do not manage finances.…”
Section: Discussionmentioning
confidence: 99%
“…Research in Banyumas 60 and Aceh 40 , as well as other countries in Ethiopia 24,61 , also found similar things. Several other studies also found higher stunting in fathers with low education 27,32,[62][63][64][65] and no education 21,22,26 . Father's education was related to stunting in this study (Table 1).…”
Section: Resultsmentioning
confidence: 78%
“…Most of the stunted toddlers were found in fathers with a height < 162 cm (Table 1). Previous research showed fathers with heights < 160 cm 62 and < 165 cm 60 were more likely to have stunted toddlers. Research in the Philippines found that fathers under 5 feet tall were 4.7 times more likely to have stunted children than their counterparts over 5 feet tall 34 .…”
Section: Resultsmentioning
confidence: 91%
“…Sepuluh intervensi telah diterapkan di Afghanistan sampai tingkat tertentu dan termasuk suplementasi asam folat perikonseptual, suplementasi protein energi seimbang ibu, suplementasi kalsium ibu, suplementasi multi mikronutrien pada kehamilan, promosi menyusui, makanan pendamping yang tepat, pemberian vitamin A dan suplementasi zinc preventif dalam anak usia 6-59 bulan, dan skrining dan pengelolaan malnutrisi akut dan kronis. Penargetan sangat penting untuk implementasi intervensi nutrisi berdampak tinggi pada skala besar (Kim, et al, 2020).…”
Section: Pembahasanunclassified